Oxidative stress genes define two subtypes of triple-negative breast cancer with prognostic and therapeutic implications - Liu, Shenting; Xu, He; Feng, Ying; Kahlert, Ulf D.; Du, Renfei; Torres-de la Roche, Luz Angela; Xu, Kai; Shi, Wenjie; Meng, Fanshuai (Frontiers in Genetics, 2023)
Background Although oxidative stress-related genes have been confirmed to be closely related to the prognosis of triple-negative breast cancer patients, there is still a lack of TNBC subtype strategies based on this gene guidance.Here, we aimed to explore OS-related subtypes and their prognostic value in TNBC. Methods: Data from TCGA-TNBC and SRA(SRR8518252) database, removing batch effects using a combat method before analysis. Consensus clustering analysis identified two OS subtypes (cluster A and B), with cluster A showing a better prognosis. Immune infiltration characteristics were analyzed using ESTIMATE and ssGSEA algorithms, revealing higher ImmuneScore and ESTIMATEscore in cluster A. Tumor-suppressive immune cells, HLA genes, and three immune inhibitors were more prevalent in cluster A. Results An eight-gene signature, derived from differentially expressed genes, was developed and validated as an independent risk factor for TNBC. A nomogram combining risk score and clinical variables accurately predicted patient outcomes. Finally, we also validate the classification effect of subtypes, by hub makers of each subtype in the test dataset. Conclusions Our study reveals distinct molecular clusters based on OS-related genes to better clarify the ROS-mediated progression and the crosstalk between ROS and TME in this heterogenetic disease as well as construct a risk prognostic model which could provide more support for the clinical treatment decisions.